Comparative Analysis of Institutional Structures and Fundamental Principles of the Criminal Justice Systems of Indonesia and South Korea - Bandu , Sri J. Anggun; Panggabean, Mompang L.; Siregar, Rospita Adelina (Universitas Medan Area, 2025)
This study aims to analyze and compare the institutional structure and basic principles of the Criminal Justice System (CJS) in Indonesia and South Korea. This study examines how the adaptation of Civil Law principles shapes the unique dynamics of the criminal justice process in both countries. Indonesia and South Korea are both rooted in the Civil Law tradition that upholds the principles of legality and codification. This study uses a normative legal method with a comparative approach through a literature review to analyze relevant legislation and literature. The results of the study show significant differences in implementation: Indonesia maintains an integrated criminal justice system model with a sectoral separation of the functions of investigators (the police) and prosecutors (the attorney general's office). In contrast, South Korea shows a more dynamic evolution through the centralization of the authority of prosecutors as leaders of investigations and the application of the limited principle of opportunity (Opportunitätsprinzip). This adaptation, including the participatory jury system as a foreign element, aims to improve efficiency, public accountability, and substantive justice-particularly in victim protection. In conclusion, South Korea’s strategy offers valuable insights for Indonesia to strengthen inter-agency integration, improve victim rights protection, and examine the potential flexibility in the principle of legality for the sake of a more equitable and effective CJS/SPP.